Effect of the use of the coordination (speed) ladder on the level of technical preparedness and the development of psychophysiological functions of young volleyball players 14-16 years old - Y.O. Goloborodko; Zh.L. Kozina; S.B. Polishchuk; A.I. Chuprina; S.A. Glyadya; Yu.K. Vasilyev (H.S. Skovoroda Kharkiv National Pedagogical University, 2018)
Purpose: theoretical substantiation and development of the methodology for using the coordination (high-speed) ladder to improve the technical skills and psychophysiological functions of young volleyball players. Material and methods. The study involved 24 volleyball players from the Municipal Institution «Comprehensive Children and Youth Sports School No. 8» (13-16 years), 12 athletes entered the control group, 12 in the experimental group. The experiment was conducted during one month in the preparatory period at the stage of basic training of the third year of training. The experimental group was trained with a coordination ladder. At the beginning and at the end of the experiment, psychophysiological testing was conducted: indicators of a simple and complex reaction were determined in various modes of signaling, and indicators of the efficiency of the nervous system. Also, athletes were tested for technical and physical preparedness. Intergroup and intra-group differences in the tests were determined. Results. The construction of a training and training process in volleyball with the use of a coordination ladder with a rapid change in the type of activity had a positive effect on the psychophysiological state of volleyball players. The obtained data testify to the advisability of using a coordination ladder with the subsequent performance of another kind of activity as an attacking blow and receiving the ball from the bottom in the training of young volleyball players to optimize the psychophysiological state. Conclusions. The influence of the application of the coordination (high-speed) ladder on the psychophysiological state of young volleyball players is determined. The method of application of the coordination ladder proposed in the work makes it possible to effectively increase the mental, physical and technical preparedness of young volleyball players within a short period of time. The developed method of using the coordination (high-speed) ladder is an effective, accessible and reliable means of improving the psychophysiological state, increasing the level of physical and technical preparedness of young volleyball players.